TINJAUAN SOSIOLOGI HUKUM TERHADAP PENGATURAN SANKSI SOSIAL DALAM MEMBERANTAS PERILAKU MENYIMPANG KORUPSI DI INDONESIA KONTEMPORER - Hannan, Abd; Syarif, Zainuddin (Program Studi Hukum Keluarga Islam, 2023)
Corruption is one of the crucial problems in Indonesia which until now has not been able to be handled. Corruption occurs in almost all lines and structures of government, from the executive, and legislature to the judiciary, from government at the central level to the regional level. This research has the specific objective of examining the regulation of social sanctions in eradicating corruption in Indonesia from a sociological perspective. Methodologically, this research is library research conducted using a qualitative approach. After analyzing field data using the perspectives of legal sociology and corruption sociology, this study found that the idea of eradicating corruption through setting social sanctions from a sociological perspective means exile or castration. Social sanctions in this context contain the meaning of maximizing the social structure and institutions of society in an effort to exercise direct control as much as possible, both in the process of prevention and prosecution. These social institutions include educational institutions, political institutions, family institutions, religious institutions, and of course legal institutions.